PENGAWASAN DISTRIBUSI GAS LPG 3 KG PADA SUB AGEN DI KECAMATAN KELUA KABUPATEN TABALONG - Rahmadi; Rahma Yuliani; Taufik Arbain (stiatabalong.ac.id, 2022)
ABSTRACT This study aims to analyze and describe the supervision of the distribution of 3 kg lpj gas in sub-agents in Kelua District, Tabalong Regency and identify inhibiting and supporting factors in the process of supervising the distribution of 3 Kg LPG gas in sub-agents. The method used is a descriptive qualitative research method with three data collection techniques, namely interviews, observations and documentation. The results showed that the supervision carried out was still low, judging from the lack of supervision when setting implementation standards in distribution. Weak supervision when determining the measurement of the implementation of activities in gas distribution. At least supervisory activities are carried out to measure the implementation of lpg gas distribution activities. Low supervision in the comparison of the implementation of activities with the standards of implementation and evaluation of deviations in the distribution of 3 kg lpg gas to sub-agents. However, for the taking of corrective measures against sub-agents when the distribution of lpg gas by the disperindag is good. Influencing factors are inadequate human resources, lack of government coordination with society, public awareness. Supporting factors are adequate human resources, and coordination. The results of this study suggest that sub-agents exist in each village evenly, increase human resources, carry out regular and continued supervision, provide rewards to sub-agents and the community, give a stern warning when there is a violation.